Assessment of Adult Psychopathology Meta-Analyses and Implications of Cross-Informant Correlation. [article]. - Achenbach, Thomas M.
Assessment of adult relies heavily on self-reports. To determine how well self-reports agree with reports who know the person being assessed, the authors examined 51,000 articles published over 10 years in 52 peer-reviewed journal for correlations between self -reports informants reports. Qualifying correlations were found in 108 (0.2%) of the articles. When self-reports and informants' reports were obtained with parallel instruments mean cross informants correlations were .681 for substance use, .428 for internalizing, and .438 externalizing problems. When based on different instruments, the mean cross-informant correlation was .304. The moderate sizes of the correlations argue for systematically obtaining multi-informant data. National survey findings were used to illustrate particularly ways to obtain and use such data. -- (from the author)
Keywords: Psychology-Periodicals.; Psychopathology; Cross-informant correlations; Multi-informant data; National survey; Self-reports.